Blood on snow : a novel - Nesbø, Jo, 1960- (Alfred A. Knopf, 2015)
"From the internationally acclaimed author of the Harry Hole novels--a new, electrifying stand-alone thriller set in Oslo in the 1970s: the story of an unusually complicated contract killer--the perfectly sympathetic antihero--that is, as well, an edgy, almost lyrical meditation on death and love. This is the story of Olav: an extremely talented "fixer" whose unexpected capacity for love is as far-reaching as his talent for murder. He works for Oslo's crime kingpin, "fixing" anyone who causes him trouble. But it's becoming clear to Olav that the more you know about your boss's business, the more your boss might want you fixed yourself, especially if you've fallen in love with his wife..."--